A phenomenological model of the mechanisms of lignocellulosic biomass pyrolysis processes - Sharma, Abhishek; Pareek, Vishnu; Wang, Shaobin; Zhang, Z.; Yang, H.; Zhang, Dong-Ke (Elsevier, 2014)
A comprehensive particle scale model for pyrolysis of biomass has been developed by coupling the reaction mechanisms and transport phenomena. The model, which also accounts for the combined effect of various parameters such as particle shrinkage and drying, was validated using available experimentaldata from the literature. The validated model was then used to study the effect of operating temperature and biomass particle size, both of which strongly influenced the rate of biomass conversion. For example, for particle sizes less than 1 mm, a uniform temperature throughout the particle was predicted, thus leading to higher conversion rates in comparison to those in the larger particles. On the other hand, any increase in moisture content led to considerable decrease in the rate of biomass conversion. For the operating conditions considered in this study, the volumetric particle shrinkage also increased the decomposition of biomass to end products.